Humanisme Islam Nusantara dan Kontribusinya Bagi Dunia - Kolek, Deodatus (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2017)
The term ‘Islam Nusantara’ (Archipelagic Islam) has been used not only to cover the Indonesian territory but also the neighboring countries. The term contains humanistic values and humanism, people in humane face, tolerance and moderate. All this reflects Islam as religion of peace. Besides it could contribute for promoting humanistic values as well as peace in the world.Such humanistic appearance of ‘Islam Nusantara’ adapts local genius of the country and highly regarded traditions of the local peoples before the coming of Islam. This accommodation could avoid any kind of both physical and verbal violences from the society and keep the people away from any possible harmful act toward their neighbour.